The biological basis of the experience and categorization of colour. (23rd September 2019) - Zeki, Semir; Javier, Alexandre; Mylonas, Dimitris
Abstract: We used the Land Colour Mondrian experiments in a Bayesian context to test the degree to which subjects vary in categorizing the colour of different patches, when each patch is made to reflect light of the identical wavelength‐energy composition. The brain uses a ratio‐taking mechanism to determine the ratio of light of every waveband reflected from a surface and from its surrounds. Our (Bayesian) hypothesis was that this ratio‐taking mechanism is similar in all humans and therefore leads to a constant categorization of colours that differs little between them. The similarly categorized colours are the initial priors, with initial hues attached to them. Twenty subjects of different ethnic and cultural backgrounds, for all but one of whom English was not the primary language, viewed eight patches of different colour in two Mondrian displays; each patch, when viewed, was made to reflect identical ratios of long‐, middle‐ and short‐wave light. Subjects were asked to match the colour of the viewed patch with that of the Munsell chip coming closest in colour to that of the viewed patch, without using language. In terms of hue, there was less variability in matching warm hues than cool ones. In terms of colour categorization, there was little variability overall. We take the lack of significant variability between subjects in the matches made as a pointer to similar computational mechanisms being employed in different subjects to perceive colours, thus permitting them to assume that their categorization of colours has universal agreement and assent. Abstract : When surfaces of different colour (for example green and yellow) that are part of complex multicoloured scenes are made to reflect the same amounts of long‐ (red), middle‐(green), and short‐wave (blue) light, human subjects belonging to different ethnic and cultural groups categorize them in the same way when asked to match them with standard coloured chips, without the use of language. The paper by Zeki, Javier and Mylonas explains why.